1994
DOI: 10.1128/iai.62.4.1381-1391.1994
|View full text |Cite
|
Sign up to set email alerts
|

Similarity between the 38-kilodalton lipoprotein of Treponema pallidum and the glucose/galactose-binding (MglB) protein of Escherichia coli

Abstract: The recent discovery that abundant and immunogenic lipoproteins constitute the integral membrane proteins of Treponema pallidum has prompted efforts to investigate their importance in the physiology and ultrastructure of the organism and in immune responses during infection. Earlier studies identified a 38-kDa lipoprotein of T. pallidum believed to be specific to the pathogen. In the present study, monoclonal antibodies generated against the 38-kDa lipoprotein of T. pallidum reacted with cognate 37-kDa molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 96 publications
(110 reference statements)
2
11
0
Order By: Relevance
“…Although a general consensus motif based upon known E. coli and B. subtilis methylation sites was utilized as the basis for such assignments (18,67), the three sites do not precisely match the consensus; the assignments of these methylation sites thus remain putative until more precise information can be obtained. Interestingly, by inference from other studies (4,17), it is predicted that CheR and CheB, which are involved in the methylation and demethylation of MCPs (67,68), exist in T. pallidum. If so, treponemal CheR and CheB may exhibit specificity for methylation and demethylation of Mcp1 somewhat divergent from the known specificities displayed by E. coli and B. subtilis CheR and CheB (67,68).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Although a general consensus motif based upon known E. coli and B. subtilis methylation sites was utilized as the basis for such assignments (18,67), the three sites do not precisely match the consensus; the assignments of these methylation sites thus remain putative until more precise information can be obtained. Interestingly, by inference from other studies (4,17), it is predicted that CheR and CheB, which are involved in the methylation and demethylation of MCPs (67,68), exist in T. pallidum. If so, treponemal CheR and CheB may exhibit specificity for methylation and demethylation of Mcp1 somewhat divergent from the known specificities displayed by E. coli and B. subtilis CheR and CheB (67,68).…”
Section: Discussionmentioning
confidence: 81%
“…This sequence also appears in the C termini of the four known E. coli MCPs, with the exception of a single amino acid substitution (NAAVEAA) (7). To minimize unnecessary degeneracy, codon preferences for T. pallidum (1,4,28,52,70,76) were taken into account in the design of MCP-2.…”
Section: Intrinsic Radiolabeling Of T Pallidum Proteins With L-[meth-mentioning
confidence: 99%
See 2 more Smart Citations
“…Except for the N-terminal residue, there were no other cysteines in the mature polypeptide. Typicat of other spirochaetal lipoproteins (Akins et al, 1993;Becker et al, 1994;Bergstrom et aL, 1989;Lam et aL, 1994;Fuchs et aL, 1992;Norris et aL, 1992;Hsu etal., 1989), hydrophilicity analysis revealed that the mature polypeptide was hydrophilic and did not contain large stretches of hydrophobic residues consistent with transmembrane domains (data not shown).…”
Section: Genetic and Antigenic Characterization Of Bbk210 An Ospf Hmentioning
confidence: 99%